LIQUIDITY RATIO ANALYSIS IN MEASURING FINANCIAL PERFORMANCE BEFORE AND AFTER THE PANDEMIC COVID-19 AT PT. SELAMAT SEMPURNA TBK - Rico Nur Ilham; Thasrif Murhadi; Reza Juanda; Fuadi; Muttaqien (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
To find out how the company's financial performance was before and during the Covid-19 pandemic, it is necessary to analyze financial reports, one of the analytical techniques is the financial ratio analysis technique. Financial ratio analysis generally consists of liquidity ratios, activity ratios, solvency ratios and profitability ratios. In this analysis, the ratio used is the liquidity ratio using the current ratio and quick ratio.This research uses secondary data where financial report data is taken from the Indonesia Stock Exchange (BEI) at www.idx.co.id The data is in the form of financial reports which are the object of this research, which consist of balance sheets and profit and loss reports for the 2018 - 2021 period. The data source used was obtained directly, namely by using financial report documents of Retail Trade Subsector companies listed on the Indonesian Stock Exchange.It can be seen that in 2018 the current ratio value of PT Selamat Selamat Tbk was found to be 394.32% and increased by 69.33% in 2019. In 2020, while the Covid-19 pandemic was taking place, it actually experienced an increase of 11.41% from in 2019. And in 2021 it experienced a decrease of 158.53% from 2020.It can be seen that in 2018 the quick ratio value was found to be 233.02% and increased by 60.72% in 2019. In 2020, while the Covid-19 pandemic was taking place, it actually experienced an increase of 101.45% from in 2019. And in 2021 it experienced a decrease of 141.98% from 2020.